Efficient simultaneous excision of multiple selectable marker cassettes using I‐SceI‐induced double‐strand DNA breaks in Saccharomyces cerevisiae. Issue 5 (27th June 2014) - Solis‐Escalante, Daniel; Kuijpers, Niels G.A.; van der Linden, Franka H.; Pronk, Jack T.; Daran, Jean‐Marc; Daran‐Lapujade, Pascale
Abstract Large strain construction programs and functional analysis studies are becoming commonplace in Saccharomyces cerevisiae and involve construction of strains that carry multiple selectable marker genes. Extensive strain engineering is, however, severely hampered by the limited number of recyclable marker genes and by the reduced genome stability that occurs upon repeated use of heterologous recombinase‐based marker removal methods. The present study proposes an efficient method to recycle multiple markers in S. cerevisiae simultaneously, thereby circumventing shortcomings of existing techniques and substantially accelerating the process of selection–excision. This method relies on artificial generation of double‐strand breaks around the selection marker cassette by the meganuclease I‐SceI and the subsequent repair of these breaks by the yeast homologous recombination machinery, guided by direct repeats. Simultaneous removal of up to three marker cassettes was achieved with high efficiencies (up to 56%), suggesting that I‐SceI‐based marker removal has the potential to co‐excise an even larger number of markers. This locus‐ and marker‐independent method can be used for both dominant and auxotrophy‐complementing marker genes. Seven pDS plasmids carrying various selectable markers, which can be used for PCR‐based generation of deletion cassettes suited for I‐SceI marker recycling, are described and made available to the scientific community.